Statistical mechanics for chemistry and materials science - Bagchi, B. (Biman) (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
'This book covers the broad subject of equilibrium statistical mechanics along with many advanced and modern topics such as nucleation, spinodal decomposition, inherent structures of liquids and liquid crystals. Unlike other books on the market, this comprehensive text not only deals with the primary fundamental ideas of statistical mechanics but also covers contemporary topics in this broad and rapidly developing area of chemistry and materials science'--
Probability and statistics - Fundamental concepts and postulates of statistical mechanics - Liouville theorem and Liouville equation - Ensembles and partition function: from postulates to formulation - Fluctuations and response functions - Ideal monoatomic gas: microscopic expression of translational entropy - Ideal gas of diatomic molecules: microscopic expression for rotational and vibrational entropy and specific heat - Quantum statistics and Bose-Einstein condensation - Lattice models - Distribution functions of liquids - Hard core interactions - Perturbation theories of liquid - Cell theory and the concept of free volume and communal entropy in liquids - Scaled particle theory and calculation of chemical potential - Phase transitions: elementary concepts - Critical phenomena: universality, scaling and renormalization - Cluster expansion and Mayer's theory of condensation - Yang-Lee theory - Classical density functional theory - Surface phenomena - Theory of freezing and melting Nucleation, Ostwald step rule and nanomaterial synthesis - Spinodal decomposition and pattern formation: evolution of structure through dynamics - Binary mixtures: towards understanding non-ideality and osmotic pressure - Inherent structures and energy landscape view of liquids and glasses - Polymer in solutions and polymer collapse - Computer simulation methods - Free energy calculations using computer simulations.
Includes bibliographical references and index.
Keywords: Statistical mechanics